Anti-Racism Representation in Song on Ecrit Les Murs (Van Dijk Frame) - Simorangkir, Imelda Malawaty; Sofiani, Yulia (Universitas Negeri Medan, 2023)
This research uses French songs. The song is called On Ã©crit sur les murs. This song is sung by Kids United, which is a children's singing group, consisting of six people. This arts group is a group formed by UNICEF. The researchers used van Dijk's critical discourse theory, which is used to dissect the meaning in the lyrics of the song On Ã©crit sur les murs Therefore, the purpose of this reseacrh is to find the meaning of the description of the macro-micro thematic system, proposed by van Dijk This research used a descriptive qualitative method. The research techniques in this research were listening, translating and analyzing song lyrics. The result of the research is that this song conveys anti-racism. They poured their feelings on a wall. Walls are used as a circle image, because many children everywhere often write on walls, especially walls on main roads to express their aspirations.